2006
DOI: 10.1167/iovs.06-0201
|View full text |Cite
|
Sign up to set email alerts
|

CD4+PD-1+T Cells Acting as Regulatory Cells during the Induction of Anterior Chamber-Associated Immune Deviation

Abstract: CD4+PD-1+ T cells from ACAID mice, as regulatory cells, are involved in the induction of antigen-specific suppression in association with enhanced expression of IL-10. CD4+PD-1+ T cells in the murine spleen may represent a substantial population of regulatory T cells possibly responsible for the induction of ACAID after intracameral injection of antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
(24 reference statements)
3
19
0
1
Order By: Relevance
“…However, as we recently reported, CD25 depletion alone had no effect on tumor growth (16), suggesting that the CD4 ϩ suppressive T cell pool that we identified in the current study may be composed of other non-T regulatory suppressive cell types as well. Indeed, the existence of PD-1 ϩ CD4 T cells acting as regulatory T cells has recently been reported (36). Our preliminary data show that ICOS high CD4 T cells, purified from ϩ NKT cells exert their immunosuppressive functions through IL-13 (37,38).…”
Section: Discussionsupporting
confidence: 52%
“…However, as we recently reported, CD25 depletion alone had no effect on tumor growth (16), suggesting that the CD4 ϩ suppressive T cell pool that we identified in the current study may be composed of other non-T regulatory suppressive cell types as well. Indeed, the existence of PD-1 ϩ CD4 T cells acting as regulatory T cells has recently been reported (36). Our preliminary data show that ICOS high CD4 T cells, purified from ϩ NKT cells exert their immunosuppressive functions through IL-13 (37,38).…”
Section: Discussionsupporting
confidence: 52%
“…Our earlier work has shown that CD4 + PD-1 + T cells played a potent regulatory role in ACAID. PD-1, a negative regulatory molecule in the CD28/B7 family, may be a marker for CD4 + regulatory cells [14]. In the present paper, our experiments showed that the frequency of Tregs was significantly increased in ACAID mice compared to the non-ACAID groups.…”
Section: Discussionsupporting
confidence: 61%
“…In fact, PD-1 is abundantly expressed in diseases associated with increased IL-10 generation such as lung, ovary, and colon carcinoma (32,33) and HIV infection (34,35). In contrast, PD-1/ PD-L1 interactions modulate positive and negative selection in the thymus (36,37) and protect immune privileged sites such as the placenta (38,39) and the eye from immune responses (40,41).…”
Section: Discussionmentioning
confidence: 99%